Perancangan Ide Bisnis Buku Cerita Interaktif All About Todd - Merlyn Olivia Sanjaya; Hutomo Setia Budi (Universitas Ciputra Surabaya, 2017)
This initiative is designed for children with the age range between 3 to 5 years old as there is an observed growth in dependency on technology among these children. This dependency has been shown to have a negative impact when there is no adult supervision. Furthermore, there is very little morale education since a young age and a lack of interest in reading which contributes to this ongoing issue. The methods which are used in this observation are literature study and interactive qualitative study by conducting interviews. From these methods combined, an interactive book, ‘All About Todd’ has been written and designed. This colorful, illustrated book contains narrated adventures as experienced by Todd, the main character of the book. This story book comes with a board game that can compete with other competitors.use of colorful illustration will help the children to understand the story told.